COVID-19 pandemic: Prevalence of depression, anxiety, and stress symptoms among Brazilian psychologists - Alvares Duarte Bonini Campos, Juliana (2022)
Introduction: Symptoms related to mental health disorders became the background of the COVID-19 pandemic, and psychologists had to adapt to the demands, while they themselves were exposed to the pandemic and its stressors. Objectives: To identify demographic and professional characteristics of Brazilian psychologists in different phases of pandemic and their reported care practices, concerns, and symptoms. Methods: This was an observational study conducted online in four independent phases with no pairing among the samples (May/June 2020, n = 263; November/December 2020, n = 131; May/June 2021, n = 378; November/December 2021, n = 222). Depression, Anxiety and Stress Scale was used. The validity and reliability of the data obtained with the DASS-21 were attested to by confirmatory factor analysis. Basic lexographic and similarity analysis were conducted to obtain textual information. Prevalence of variables was estimated and compared between phases using the z-test (α = 5%). Similarity analysis was performed to identify the psychologists’ concerns. Results: Most of participants were women and were self-employed or employed. There was rapid adjustment to remote work and more than 70% reported changes in their mental health since the onset of pandemic. One in four participants had a previous mental health disorder, and there was a high prevalence of symptoms such as anxiety, fear, and angst. The prevalence of professionals who reported not caring about their own mental health was significant. In 2020, one cluster (health) of concern was identified, while in 2021 there were three clusters (health, family, and COVID-19). The prevalence of depression, anxiety, and stress symptoms was high and did not change during the pandemic. Conclusions: Psychologists adapted to the demands of the population in the face of the pandemic. However, there was a high prevalence of mental health symptoms and a disregard for self-care among these professionals.